2002
DOI: 10.1038/sj.cr.7290125
|View full text |Cite
|
Sign up to set email alerts
|

A novel ubiquitin carboxyl terminal hydrolase is involved in toad oocyte maturation

Abstract: ABSTRACTp28, a 28kD protein from toad (Bufo bufo gargarizans) oocytes, was identified by using p13 suc1 -agarose affinity chromatography. Sequence homology analysis of the full-length cDNA of p28(Gene Bank accession number: AF 314091) indicated that it encodes a protein containing 224 amino-acids with about 55% identities and more than 70% positives to human, rat or mouse UCH-L1, and contains homological functional domains of UCH family. Anti-p28 monoclonal antibody, on injecting into the oocytes, could inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The data in Xenopus oocytes suggested that the activity of MAP kinase is essential for maintaining the activity of p90 rsk [41,42]. Previous work by us and others also showed that in mouse and rat oocytes, the change of MAP kinase activity is always followed by the change of p90 rsk activity during meiotic maturation, fertilization, and parthenogenetic activation [43][44][45].…”
Section: Discussionmentioning
confidence: 97%
“…The data in Xenopus oocytes suggested that the activity of MAP kinase is essential for maintaining the activity of p90 rsk [41,42]. Previous work by us and others also showed that in mouse and rat oocytes, the change of MAP kinase activity is always followed by the change of p90 rsk activity during meiotic maturation, fertilization, and parthenogenetic activation [43][44][45].…”
Section: Discussionmentioning
confidence: 97%
“…We have found that UCH-L1 is involved in toad oocyte maturation, and toad UCH-L1 is considered to specifically bind to CDK1 in toad oocyte protein extracts (Sun et al 2002). So, in mouse oocytes UCH-L1 may be associated with the mitotic promoting factor (MPF), also known as maturation promoting factor, which consists of cyclin B1/B2 and CDK1 (or p34 cdc2 ).…”
Section: Discussionmentioning
confidence: 97%
“…1a). It has been reported that UCH-L1 binds to CDK1 in toad oocyte protein extracts (Sun et al 2002), so we examined the protein-protein interaction of UCH-L1 and CDK1, and found that UCH-L1 was able to bind to CDK1 in mouse ovarian protein extracts (Fig. 1a).…”
Section: Ptov1 Is Specifically Bound To Uch-l1 In Ovarian Protein Extmentioning
confidence: 93%
See 2 more Smart Citations